A Ten-Year Study on the Prevalence and Frequency of Risk Factors for Breast Cancer in Sabzevar, Iran - Masoumeh Hashemian; Roya Akbarzade; Ali Asghar Khosroabadi; Zahra Sadat Asadi; Somayeh Salehabadi; Bibi Leila Hoseini (Mashhad University of Medical Sciences, 2016)
Background & aim: Evaluation of prevalence of risk factors for breast cancer in different regions of Iran and identification of their significant effect on this disease can promote the prevention and reduction of breast cancer incidence. Therefore, this study aimed to evaluate the prevalence, demographic characteristics, and frequency of the risk factors of breast cancer during 10 years. Methods:This cross-sectional study was conducted on 160 women with breast cancer during 10 years. The samples, referred by health connectors and registration centers for patients with cancer, were selected using census sampling. Research tool was a reliable and valid researcher-made questionnaire, validity and reliability of which were confirmed. Data analysis was performed in SPSS version 16 using descriptive statistics. Results: In total, mean age of surviving women was 50.7±1.2 years. The highest incidence rate of breast cancer was 35.2% in the group of participants aged 40-49, while the highest prevalence rate of this disease was 0.432 per 1000 samples in a group of patients aged 50- 59 years. Moreover, the most frequent risk factors for this disease were previous use of oral contraceptive pills (OCP) (56.8%) and positive family history (19%). Conclusion: The results of this study were indicative of positive family history as a certain risk factor for breast cancer in Sabzevar. Therefore, it is recommended that special attention be paid to women with positive family history of breast cancer. Therefore, prioritization of breast cancer screening and prevention programs is of paramount importance in this regard.